Collaborative Assembly Operation between Two Modular Robots Based on the Optical Position Feedback. (13th December 2009) - Su, Liying; Shi, Lei; Yu, Yueqing
Abstract : This paper studies the cooperation between two master-slave modular robots. A cooperative robot system is set up with two modular robots and a dynamic optical meter-Optotrak. With Optotrak, the positions of the end effectors are measured as the optical position feedback, which is used to adjust the robots' end positions. A tri-layered motion controller is designed for the two cooperative robots. The RMRC control method is adopted to adjust the master robot to the desired position. With the kinematics constraints of the two robots including position and pose, joint velocity, and acceleration constraints, the two robots can cooperate well. A bolt and nut assembly experiment is executed to verify the methods.